Cloning and analysing of cis-acting elements in the E8 promoter from tomato (Lycopersicon esculentum L.) - Hong, La Viet; Duc, Le Hoang; Son, Le Van; Ngoc, Pham Bich; Ha, Chu Hoang (Academia Journal of Biology, 2014)
Promoter is a sequence located at the 5’ end upstream of the gene, that plays a key role in gene expression. In tomato, the E8 gene is highly expressed during fruit ripening, and is controlled by E8 promoter. E8 promoter includes the cis-acting elements responding to ethylene or receiving independent signals of ethylene for fruit ripening. This study presents results of E8 promoter cloning and sequencing from the tomato cultivar PT18 for construction of vector to express target gene in tomato. The obtained data showed that the E8 promoter has 2203 bp in length and carries a full range of cis-acting elements similar to a typical promoter such as TATA box, box CAAT and GATA box. Furthermore, this promoter contains two fruit-ripening regulatory regions. Nucleotide sequences of E8 promoter had high similarity when compared with other E8 promoter sequences in Genebank. In addition, the nucleotide sequence of E8 promoter was submitted in Genebank with the accession number KJ561284. The results is the foundation that will contribute a fundamental basis for further researches in order to construct expression vector carrying E8 promoter in gene transfer of plants.